Sinergia de solventes com desemulsificantes industriais: análise e comparação da eficiência na quebra de emulsão de água em óleo de petróleos brutos - Xavier, Felipe Augusto Neres (Universidade Federal de São Carlos, 2023)
The Oil&Gas industry originated in 1859, when the first well was drilled in the United States. Since then, numerous discoveries and improvements have been made in the exploration process, from extraction to refining. Over the years, sector development research has focused on several fronts, always seeking to obtain greater exploration yields. Consequently, studies related to the water-in-oil emulsion, which constitutes crude oil, and its stabilization mechanisms gained the spotlight in research, to understand and improve the products used in the demulsification process. Studies have indicated the possibility of using different solvents with diverse chemical characteristics, such as polarity and aromaticity, to obtain a higher performance in water separation. Nowadays, there is still room for new discoveries related both to the exploration process and to the products sold by the specialized industry. Industries are still not exploring the full potential that solvents can have to increase yield or make this process greener. Because of this, this work focused on the bibliographic review of articles that seek to better understand the oil emulsion stabilization mechanism and on an overview of the mechanism of operation of demulsifiers. The information was validated from a case study. The study sought to evaluate, through a planning of solvent mixtures, the best formulation for different oils, this was possible mainly when using desirability as a methodology for analyzing the results. In this way, it was possible to compare literature results with the results obtained in the study and conclude that the mechanism proposals found in the articles seem to be consistent with the empirical part of the process, this opens the possibility of performing more in-depth studies, related to the synergy of solvents with commercial demulsifying bases to improve the crude-oil extraction and exploration process.
Solvent-Surfactant Synergy in Industrial Demulsifiers: Analysis and Comparison of Efficiency in Water-in-Oil Emulsion Breaking in Crude Petroleum
Keywords: Desemulsificantes; Petróleo; Solventes; Óleo e gás; Emulsão; Planajamento de experimentos (DoE); Quimiometria; Demulsifier; Crude oil; Solvents; Oil&Gas; Emulsion; Design of experiments (DoE); Chemometrics; CIENCIAS EXATAS E DA TERRA::QUIMICA::QUIMICA ANALITICA